Design Considerations for the Development of Crowdsourcing Systems. (September 2021) - Harper, Samantha B.; Dorton, Stephen L.; Creed, Glory
We present a case study on factors that affect the usability and User Experience (UX) of a crowdsourcing platform for argumentation. While this particular system is focused on argumentation, we have aimed to abstract our findings such that they are generalizable to other use cases so that others may consider these lessons learned and recommendations for the development of more effective crowdsourcing and collaborative work platforms. Several themes were identified in participant responses about the usability and UX of the crowdsourcing system, including a desire for less structure, the need for additional training, the desire for a streamlined workflow and UI, improved navigation, and the enjoyment of interactions with other users.